Improving medical handover at the weekend: a quality improvement project. Issue 1 (25th June 2015) - Michael, Emma; Patel, Chandni
Abstract: In recent years medical handover has been identified as an increasingly important area for hospitals to improve upon, in light of the changes in shift patterns for doctors. Significant changes to weekday handover had recently been successfully introduced at Broomfield hospital. Weekend handover remained a concern, with an electronic and paper system being used simultaneously. Our objectives were to introduce a new electronic handover system for weekend handover at Broomfield Hospital and improve the organisation of the weekend handover meeting to promote patient safety. Doctors involved in weekend handover were surveyed using a questionnaire, to establish insufficiencies in the weekend handover process; where both the electronic ExtraMed system and paper were being used inconsistently. A new weekend handover system was introduced together with a new user-friendly electronic handover database, addressing the identified difficulties in the current system. These changes met the medical handover guidelines set by the Royal College of Physicians. Three months after the launch of the new system, doctors were re-surveyed using a modified questionnaire to assess the impact our changes had made. Before changes were implemented only 12% of doctors surveyed used the electronic system for weekend. Eighty-nine percent found sorting through jobs time consuming and 67% were handed jobs to them meant for a different grade of doctor. Only 41% were aware who to hand weekend discharges to. Subjective assessment of safety was 3.18 out of 5. The electronic system was felt to be time consuming and complicated. After execution of the new weekend handover process, 100% of doctors reported using the electronic system for weekend handover. Only 47% of doctors felt sorting through jobs was time consuming and 89% of doctors were aware who to handover weekend discharges to. Subjective assessment of the safety of weekend handover improved to 3.84 out of 5. Informal interviews on the ward revealed a high degree of satisfaction with the new weekend handover system. In conclusion we found that a structured, well organised weekend handover meeting together with an effective electronic handover system improves the quality of medical weekend handover.